Assessing the Role of Teacher Training and Professional Development in Enhancing Early Childhood Education in Katsina State, Nigeria - Bakori, Nura Garba (Sahel Journal of Life Sciences FUDMA, 2024)
This research examines the effectiveness of teacher training and professional development programs in enhancing early childhood education in Katsina State, Nigeria. Data was collected on teacher training and professional development in enhancing early childhood across three geopolitical zones of Katsina State. Daura; Katsina; and Funtua. Considered four Local Government Areas in each. A total of 180 teachers and 20 schools participated in the survey. The review synthesizes existing research on teacher training, professional development, and early childhood education, highlighting the challenges and opportunities for improvement. The findings suggest that well-structured teacher training and professional development programs can significantly improve teacher quality, student outcomes, and educational standards in Katsina State.